M11 Nintedanib and pirfenidone for idiopathic pulmonary fibrosis (IPF) in north east england – real life data. (12th November 2019) - Murphy, CJ; Donaldson, C; Langlands, L; Wiscombe, S; Simpson, AJ; Forrest, IA
Abstract : Introduction: Licensed anti-fibrotic medication (AFM) for IPF is limited to Pirfenidone and Nintedanib. Pirfenidone has been prescribed by the Newcastle Interstitial Lung Disease Service (NILDS) since March 2014 and Nintedanib since December 2015. Patients are referred to the NILDS by twelve regional trusts. Diagnosis of IPF is confirmed by the NILDS MDT before patient assessment for suitability of AFM. Methods: Multi-centre retrospective cohort review of all patients on Pirfenidone and Nintedanib since the beginning of local AFM prescription. Aims: Evaluation of the basic characteristics of non-trial, 'real life' patients on AFM in a North East cohort. Results: Up until June 2018, 194 patients had been prescribed Pirfenidone, 98 (50.5%) had stopped it, 45 (23.2%) were still taking it and 51 (26.3%) patients had died on Pirfenidone. Diagnoses for patients on Pirfenidone were definite IPF (n=107, 55.2%), working diagnosis IPF (n=21, 10.8%), probable IPF (n=45, 23.2%), Combined Pulmonary Fibrosis and Emphysema (n=20, 10.3%) and others (n=1, 0.5%). Of those stopping Pirfenidone, 37 (37.7%) patients switched to Nintedanib. Mean age for patients taking Pirfenidone was 73 years, 85% males. 212 patients had been prescribed Nintedanib, 62 (29.2%) had stopped it, 113 (53.3%) were still taking it and 37 (17.5%) patients had died on Nintedanib. Diagnoses for patients on Nintedanib were definite IPF (n=106, 50.0%), working diagnosis IPF (n=33, 15.6%), probable IPF (n=36, 17.0%), CPFE (n=36, 17%) and others (n=1, 0.4%). Of those stopping Nintedanib, 26 (41.9%) patients switched to Pirfenidone. Mean age for patients taking Nintedanib was 72 years, 81% males. In both treatment cohorts most patients had more than one side effect cited as the cause for stopping medication (see table 1). Mean treatment duration at last known patient contact was 12.2 months (range 1–46) for Pirfenidone and 10.1 months (range 1–34) for Nintedanib. Conclusions: Gender and age distribution for both AFM groups was similar to other UK IPF patient cohorts. Longer treatment duration in the Pirfenidone group may be due to increased length of medication availability. Side effects are often multiple in nature but both AFMs can be tolerated with specialist support for an extended period of time.